Analysis of the Shear Stress State at the Native Material/Repair Material Interface in Cooling Towers - Kutylowski, Ryszard (Periodica Polytechnica Civil Engineering, 2023)
The structure of the cooling tower shell locally made of materials differing in their specifications is considered. Such structures are created as a result of cooling tower shell repairs or reinforcements. The results of an analysis of the distribution and magnitude of shear stress at the interface between layers made of different materials are presented.